2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6654786
|View full text |Cite
|
Sign up to set email alerts
|

DTM<sup>2</sup>: Adapting job market signaling for distributed trust management in vehicular ad hoc networks

Abstract: Abstract-In this paper, we address the issue of the presence of malicious and selfish nodes in Vehicular Ad Hoc Networks (VANETs). Malicious nodes spread false and forged messages, while selfish nodes only cooperate for their own interest. To deal with this, we propose DT M 2 , a Distributed Trust Model inspired by Spence's Job Market model from Economics. In our model, a sender node transmits a signal with its message. This signal represents a guarantee of the truthfulness of the message for the potential rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The simulation results showed that the authors achieved higher energy efficiency and security level optimization based on QoS and energy demands 16 . Haddadou and Rachedi 17 proposed a method to detect and evict all malicious nodes in a network. Furthermore, the method significantly reduces the percentage of erroneous and misleading data delivered via a network to as low as 0% when increasing the participation ratio of selfish nodes by 20%.…”
Section: Related Workmentioning
confidence: 99%
“…The simulation results showed that the authors achieved higher energy efficiency and security level optimization based on QoS and energy demands 16 . Haddadou and Rachedi 17 proposed a method to detect and evict all malicious nodes in a network. Furthermore, the method significantly reduces the percentage of erroneous and misleading data delivered via a network to as low as 0% when increasing the participation ratio of selfish nodes by 20%.…”
Section: Related Workmentioning
confidence: 99%
“…A direct trust evaluation strategy that is inspired by the job market signalling model is proposed in [43], where the sender transmits a signal with its message to ensure the truthfulness of that message for the receiving vehicles. To use the signal, the sender is charged, and the cost depends on the value of the signal and its own behaviour.…”
Section: Direct Trust Modelmentioning
confidence: 99%
“…In another example [42], when a trustor receives a message from a potential trustee, the current trust value TR cur is calculated as STnnormalT=γ×STcur+false(1γfalse)×STn1normalT,1emST0normalT=0.5where TnormalRcur=STnnormalT. The satisfaction level ST is defined using the number of successful operations N suc and the number of failed operations N fail during multiple packet delivery as follows: ST= Nsuc+1Nfail+Nsuc+2A direct trust evaluation strategy that is inspired by the job market signalling model is proposed in [43], where the sender transmits a signal with its message to ensure the truthfulness of that message for the receiving vehicles. To use the signal, the sender is charged, and the cost depends on the value of the signal and its own behaviour.…”
Section: Trust Evaluation Models For Vehicular Networkmentioning
confidence: 99%
“…Their work is featured by good scalability and thus potential in many applications. DTM 2 [13] is a distributed trust model inspired by Job Market model. With the help of third party hardware, system could incent good behaviors and punish malicious behaviors by changing each vehicle's signal value.…”
Section: Related Workmentioning
confidence: 99%